A critical analysis of the relationship between commemoration, meaning and landscape design in Post-Apartheid South Africa : Isivivane, Freedom Park - a case study - Vosloo, Pieter Tobias (University of Pretoria, 2020)
Dissertation (MLandscape Architecture)--University of Pretoria, 2019.